Auslander Reiten Quiver of Nakayama Algebra Nn-2,n - Faisal Faisal; Irawati Irawati; Intan Muchtadi Alamsyah (Jurnal Matematika & Sains, 2013)
For an algebraically closed field K, given a finite dimensional K-algebra A ofÂ  finite representation-type, we can store all the information of the module category mod A by its Auslander Reiten quiver of mod A. In this paper, we will determine the Auslander Reiten quiver of Nakayama algebra Nn-2,n Â for every natural number n greater than or equal to 3, that is theÂ  Nakayama algebra KQ/I where Q is a linear orientation cyclic quiver with Â vertices and Â denotes the ideal of the path algebra KQ generated by the paths of length of n â 1. Keywords: AR-quiver , Nakayama algebra, Quiver. Â  Quiver Auslander Reiten dari Aljabar Nakayama Nn-2,n AbstrakDiberikan K-aljabar A berdimensi hingga tipe representasi hingga dengan K suatu lapangan yang tertutup secara aljabar, Â kita dapat menyimpan semua informasi dari kategori modul kanan mod A menggunakan Auslander Reiten quiver (AR-quiver) dari mod A. Dalam artikel ini, kita akan menentukan quiver Auslander Reiten dari aljabar Nakayama untuk setiap bilangan asli n lebih besar sama dengan 3. Aljabar Nn-2,n adalah aljabar Nakayama KQ/I dimana Q adalah quiver siklis berorientasi linier dengan Â titik dan I adalah ideal dari aljabar lintasan KQ yang dibangun oleh lintasan panjang n â 1. Kata Kunci : AR-quiver, Aljabar Nakayama, Quiver.